PERFORMANCE MEASUREMENT AND IMPROVEMENT STRATEGY ON SERVICE FACILITY OF SOEKARNO HATTA AIRPORT TERMINAL 3 - Miranda, Nabila Mira; Mulyono, Nur Budi (Journal of Business and Management, 2018)
Abstract.Background: As the main gateway of Indonesia, Soekarno Hatta Airport handled 63 million air transportation passengers in 2017, while the capacity per year is 62 million passengers. The growth of air transport service users in Indonesia continues to increase in consequence of the increasing number of airlines in Indonesia offer low cost of air travel. Along with the increasing number of peoples traveling by airplane, it is importance to know the condition and suitability of space availability and the service facilities performance from airport service userâ€™s perceptions. The aim of this study is to measure the performance of service facilities provided in Soekarno Hatta Airport Terminal 3 based on airport service userâ€™s interest. Methods: Importance Performance Analysis conducted from the data based on 400 answer questionnaires by the airport service users to analyze their interest and perception on 21 airport service facilities. Results: Soekarno Hatta Airport Terminal 3 management need to improve the technology-based facilities, staff helpfulness, check in processing time, and baggage delivery processing time. Conclusions: To overcome the problems of lack of performance on service facility, writer suggest that Soekarno Hatta Airport Terminal 3 management to develop more self-service technology.Keywords: Performance Measurement, Improvement Strategy, Importance Performance Analysis, Service Facility, AirportÂ